Simulation of two-phase flow and mass transfer of CO2 bubbles in a sweetener solution by horizontal pipe using Comsol - Nsaif, Ahmed Dheyaa; Shakir, Ibtehal Kareem; Al-Lami, Munaf (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
This research investigated the two-phase flow behavior and mass transfer of CO2 bubbles in a water-sucrose solution in a horizontal pipe. The process used A Computational Fluid Dynamic (CFD) model that offers diverse applications in numerous industries. The simulation of two-phase flow with mass transfer is carried out using COMSOL® software version 5.6 and compared with experimental results. The model verified satisfactory concurrence with the experimental data. Multivariable such as concentration, velocity, and share rate were studied under different conditions (gas flow rate, liquid flow rate, bubble diameter, pipe diameter, and sucrose concentration). The gas flow rate was varied at the inlet, with values of (0.2, 0.45, and 0.7 L/min) for CO2 and (2, 4, and 6 L/min) for the sweeteners solution. The diameter of the bubbles ranged from (2 to 4 mm). The pipe diameter was (1.25 and 1.9 cm), and the sucrose concentration in the sweetener solution was (150 g/L). It was observed that the effect of bubble diameter was inversely to CO2 concentration, and the gas and liquid flow rates were directly proportional to concentration. The concentration of CO2 decreases as the concentration of sucrose increases. The relationship between bubble diameter and gas phase velocity was inverse, as well as studying the effect of variables on share rate.